The Effect of Hypermedia-Assisted Learning Organizing Strategies and Cognitive Styles on Student Learning Outcomes - Aisyah, Nur; Degeng, I Nyoman S; Sumarmi, Sumarmi; Toenlioe, Toenlioe (JURNAL AL-TANZIM, 2024)
This study focuses on evaluating the use of hypermedia-assisted learning content organizing strategies and their impact on the homogeneity of student learning outcomes. The main objective of this study was to assess whether the use of hypermedia can produce more even learning outcomes among students compared to conventional learning strategies. The research method used is quasi-experimental with a quantitative approach, conducted at Nurul Jadid University. Data collection techniques include learning outcomes tests and cognitive style tests, which are given before and after treatment to measure changes in learning outcomes. Data analysis using two-way analysion of variance (two-way ANOVA) with the help of SPSS software version 20. The results showed that the use of hypermedia in organizing learning content resulted in a more homogeneous distribution of learning outcomes compared to conventional methods. This finding supports previous research showing that the integration of technology in learning can improve the quality and homogeneity of teaching and learning. The implication of this research is the importance of adaptive education management and technological capacity building to support more effective and consistent learning processes.